Islamic Value-Based Self-Regulated Learning Strategy for PAI Students as The Contribution of Islamic Psychology to Civilization - Hadi, Abil Fida Muhammad Qois Al; Istanto, I; Shobahiya, Mahasri; Siati, Is Silaning; Maksum, Muh. Nur Rochim; Jamroji, Bagus; Vambudi, Viky Nur; Budihargo, Mushab Umar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to examine the application of Self-Regulated Learning (SRL) based on Islamic values by PAI students, as well as the factors that affect its success.Methodology: The research method used is qualitative with a phenomenological approach, involving interviews and observations on PAI students at the University of Muhammadiyah Surakarta. Data were analyzed descriptively to understand students' experiences and perceptions related to SRL in the context of Islamic values.Results: The study found that students used various SRL strategies, such as learning planning and self-reflection, integrating Islamic values like patience, tawakal, and sincerity. Supporting factors included intrinsic motivation, social support, and supportive facilities. Inhibiting factors included a lack of understanding of Islamic-based SRL and the influence of technology. The implementation of SRL positively impacted academic achievement and character development.Applications/Originality/Value: The study highlights the importance of integrating Islamic values into SRL to enhance both academic and moral development of PAI students, emphasizing its relevance in the context of modern education. The findings offer insights into how Islamic teachings can be applied to foster better learning outcomes and personal growth.